Peran Supplier Relationship Management (SRM) Pada Pemasok Di PT. Krakatau Pipe Industries - Fitriasyach, Khaila Priwisastra; Putri, Solehatin Ika; Affifatusholihah, Lina (UMSurabaya Publishing, 2024)
Relationship Management and the obstacles in maintaining relationships with suppliers at PT. Krakatau Pipe Industries. The method used is descriptive through observation, interviews and documentation as data collection. Results in this final project is the implementation of Supplier Relationship Management which is carried out by PT Krakatau Pipe Industries through four activities, The first activity is identifying key suppliers based on strategic criteria such as product quality, on- time delivery, competitive pricing, and flexibility in facing market changes. facing market changes. In the second activity, information sharing the company's interaction with business partners to share information and strategies together. The third activity is decision synchronization with selected suppliers for strategic discussions such as delivery schedules and raw material procurement. delivery schedules and raw material procurement help reduce conflicts and increase operational efficiency. Improve operational efficiency. Furthermore, the fourth activity is conducting supplier evaluation on a regular basis to ensure quality and service standards are met. The results are used to improve or replace unsuitable suppliers. As for the obstacles in maintaining relationships with suppliers is related to constraints in internet access for small suppliers. internet access for small suppliers. Keywords: supplier; supplier relationship management Tujuan artikel ini untuk mengetahui penerapan Supplier Relationship Management dan hambatan dalam menjaga hubungan dengan pemasok di PT. Krakatau Pipe Industries. Metode yang digunakan yaitu deskriptif. Hasil penelitian ini adalah penerapan Supplier Relationship Management yang dilakukan PT. Krakatau Pipe Industries melalui empat aktivitas, yaitu; pada aktivitas pertama melakukan identifying key suppliers berdasarkan kriteria strategis seperti kualitas produk, ketepatan waktu pengiriman, harga kompetitif, dan fleksibilitas dalam menghadapi perubahan pasar. Pada aktivitas kedua melakukan information sharing interaksi perusahaan dengan mitra bisnis untuk berbagi informasi dan menyusun strategi bersama. Aktivitas ketiga yaitu melakukan decision synchronization dengan pemasok terpilih untuk diskusi strategis seperti jadwal pengiriman dan pengadaan bahan baku membantu mengurangi konflik dan meningkatkan efisiensi operasional. Selanjutnya aktivitas keempat melakukan supplier evaluation secara rutin memastikan standar kualitas dan layanan terpenuhi hasilnya digunakan untuk memperbaiki atau mengganti pemasok yang tidak sesuai. Adapun hambatan dalam menjaga hubungan dengan pemasok yaitu terkait dengan kendala dalam akses internet bagi pemasok kecil Kata Kunci: Suplier, Manajemen Hubungan Supplier